Prueba de paternidad al presunto progenitor en los juicios de alimentos tramitados en los juzgados de la niñez y adolescencia en la ciudad de Machala en los años 2012-2013. - Pacheco Feijoo, Geovanny Cristhian (2014)
This research work aims to sound out with absolute precision the causes legal effects and other circumstances relating to the setting of temporary alimony against the defendants in the trials of foods presumption of paternity, not even been determined through scientific practice DNA, the existence of the relationship Pater-edged, indeed, such a judicial imposition has been recorded even when he was granted to the defendant his right to defense.